As percepções dos tradutores intérpretes de libras face as suas atribuições profissionais no ensino superior - Brasil, Joelaini Martins dos Reis (2021)
This study is linked to the Special Education Research Line of the Graduate Program in Education. The objective was to identify the perceptions of Interpreting Libras Translators (TILSP) regarding the exercise of their professional attribution in the context of Higher Education. The theoretical framework used permeated Brazilian legislation and studies that deal with the professional attributions of Libras interpreters in Higher Education. Through a qualitative approach, a survey was carried out with interpreters from Brazilian Federal Institutions of Higher Education in the state of Rio Grande do Sul (RS). Initially through a questionnaire on Google Forms and later, through a semi-structured interview conducted with interpreters from federal institutions and education. It was found that still, many are unaware of this profession, many are the attributions delegated to this professional. In face-to-face and virtual activities in educational contexts, the deaf have the possibility of being inserted, and the TILSP is the mediator of the speeches produced by the speaker. It was concluded that, the profession is permeated by challenges and many are the attributions delegated to this professional, the right of the deaf is guaranteed, and the TILSP is the mediator of the speeches produced in the educational context.